2002
DOI: 10.1007/s005950200002
|View full text |Cite
|
Sign up to set email alerts
|

Poor Neorectal Evacuation as a Cause of Impaired Defecatory Function After Low Anterior Resection: A Study Using Scintigraphic Assessment

Abstract: Poor neorectal evacuation is associated with impaired defecatory function after LAR. Therefore, it is suggested that optimizing both reservoir function and evacuation of the neorectum would improve defecatory function after LAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
14
2
Order By: Relevance
“…Oya et al reported that the time-activity curve of evacuation seen in cases of a neorectum closely correlated with postoperative bowel functions following anterior resection. 14 Seike et al showed that patients who complain of evacuation difficulty postoperatively tend to have a high volume of left-sided colon gas, which suggests a motility disorder at the neosigmoid or neorectum. 15 In healthy individuals who have not undergone any surgery, rectal function has been reported to play a major role in fecal continence 16 and chronic constipation.…”
Section: Discussionmentioning
confidence: 98%
“…Oya et al reported that the time-activity curve of evacuation seen in cases of a neorectum closely correlated with postoperative bowel functions following anterior resection. 14 Seike et al showed that patients who complain of evacuation difficulty postoperatively tend to have a high volume of left-sided colon gas, which suggests a motility disorder at the neosigmoid or neorectum. 15 In healthy individuals who have not undergone any surgery, rectal function has been reported to play a major role in fecal continence 16 and chronic constipation.…”
Section: Discussionmentioning
confidence: 98%
“…The above-mentioned outcome failed to gain significance between procedures. By omitting the study of Ho et al [80] for sensitivity analysis, heterogeneity was not further significant (I 2 =27.1%), but comparison did not result to statistical difference (p=0.19). In contrast, "prolonged evacuation" was significantly different in favor of colon J-pouch, and the "need for laxatives" was statistically significant in favor of SCA.…”
Section: Intermediate-term Follow-upmentioning
confidence: 51%
“…Furthermore, patients with a long segment of denervated terminal colon had a significantly prolonged transit time in the sigmoid colon and neorectum. A prolongation of terminal colonic transit correlated closely with postoperative bowel function, especially with defecation disorders [80]. A prolongation of terminal colonic transit may also be a reason for increased amounts of colonic gas observed in patients suffering from constipation after low anterior resection, as presented by Seike and co-workers [81].…”
Section: Discussionmentioning
confidence: 95%
“…These have an advantage in the ability of detecting morphological abnormality such as perineal descent and rectocele. Studies on neorectal (pouch) emptying in patients after LAR have been limited [14,24,25] although the evacuation difficulty has been reported as a common symptom after LAR, especially after colonic J-pouch anastomosis [12,13,26]. Studies on neorectal (pouch) emptying in patients after LAR have been limited [14,24,25] although the evacuation difficulty has been reported as a common symptom after LAR, especially after colonic J-pouch anastomosis [12,13,26].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous scintigraphic study in patients who had undergone stapled straight anastomosis after LAR suggested that neorectal emptying significantly affects over-all defecatory function [14]. In the present study we compared neorectal emptying after stapled LAR between colonic J-pouch and straight anastomosis using the same scintigraphic method and explored factors affecting neorectal emptying after stapled LAR.…”
Section: Introductionmentioning
confidence: 95%